Strategies to enhance thermoelectric performance: Review - Lydia Rathnam; Surabhi Suresh Nair; Arnab Ganguly; Nirpendra Singh; Gobind Das (Journal of Materials Research and Technology)
Thermoelectric (TE) technology can play a promising role in the energy landscape but its low efficiency remains a significant drawback in pratical applications. . This review gives information regarding the strategies for boosting thermoelectric performance, such as band engineering, nanostructuring, defect engineering, and Anderson Localization. Band engineering can enhance the power factor by increasing band effective mass (md∗)while maintaining high carrier mobility (μ) and increasing the conducting bands Nv. Nanostructuring techniques profoundly impact thermoelectric performance by tailoring the material's microstructure, leading to enhanced carrier scattering, reduced thermal conductivity, and improved electrical transport, thereby opening up promising avenues for high-efficiency thermoelectric applications. Defect engineering, encompassing the introduction of vacancies, nanoprecipitates, and dislocations as efficient phonon scattering centers, emerges as a compelling strategy for optimizing thermoelectric properties through enhanced phonon scattering and charge carrier transport, presenting promising prospects for advancing high-performance thermoelectric materials. Recent theoretical and experimental studies have demonstrated that thermoelectric (TE) improvement is possible through an enhanced Seebeck coefficient, achieved via Anderson localization, which is characterized by a nonzero, small electrical conductivity when the chemical potential lies below the localization threshold within a single mobility edge. This effect becomes prominent when the chemical potential lies below the localization threshold within a single mobility edge. In conclusion, the integration of nanostructuring, band engineering, defect engineering, and Anderson localization offers remarkable potential to enhance the thermoelectric properties of materials. These synergistic approaches hold great promise in unlocking the full potential of thermoelectric technology and advancing sustainable energy solutions for the future.